Enhancing Flipped Pedagogy Using JavaScript - Dhakal, Bed Prasad (AMC Journal (Dhangadhi), 2025)
Integrating innovative pedagogy using digital tools can enhance students learning in mathematics education. So, this study investigates how to effectively use flipped pedagogy, focusing specifically enhanced by javascript mathematical simulations. Over a period of four months, we implemented and observed a pedagogical intervention of enhanced flipped pedagogy in a course “Differential Geometry”, which is a third semester course of Master in Mathematics Education at Tribhuvan University, Nepal. Through a qualitative analysis rooted in design-based and grounded theory methodologies, this study placed emphasis on sixteen student’s (five girls, eleven boys) perspectives, to design and refine enhanced flipped pedagogy. The finding of the study reveal two critical elements that support the successful implementation of enhanced flipped pedagogy: (a) well-structured and purposeful task formulation and (b) centralized digital learning platforms.